PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DI POLITEKNIK LP3I JAKARTA KAMPUS KRAMAT RAYA - D Purnomo; Kania Farida; Nur Haris Ependi (JURNAL LENTERA BISNIS, 2021)
This study aims to determine how big the influence of motivation and competence on employee performance at the LP3I Polytechnic Jakarta Kramat Raya Campus. The research method used in this study is a quantitative method through questionnaires, with a population of 85 people and the sample is 85 people so that the sample calculation uses the census method. The first result of this study is that there is a significant positive effect between motivation on employee performance with an influence strength of 36.4%, the second result is that employee competence has a significant positive effect on employee performance with an influence strength of 45.5%, the third result is motivation. work and competence together affect employee performance by 49.6% while 50.4% is explained by other variables not examined in this study.Keywords: Motivation, Competence, and Employees’ Performance